Building Family Resilience in Contemporary Society: A Theoretical Analysis Informed by Family Resilience Theory and the Concept of Maslahah - Arif, Arif Sugitanata (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: In the context of modern life, characterized by rapid technological advancements, significant social transformations, and escalating economic pressures, families encounter multifaceted challenges. Objective: This study aims to delineate efforts to enhance family resilience in contemporary society, analyzed through two theoretical frameworks: family resilience theory and the concept of maslahah. Methods: This research employs a literature review supplemented by descriptive-analytical analysis to identify the factors that contribute to family resilience. Family Resilience Theory underscores the critical role of open communication, emotional support, flexibility, and character education in fostering resilience. Results: The findings indicate that families exhibiting effective communication and robust emotional support are better positioned to navigate challenges such as technological demands and economic difficulties. Furthermore, ongoing character education and families’ adaptability to social changes are essential components in fortifying their resilience. The maslahah theory, which emphasizes the fulfillment of public interests and the prevention of harm, accentuates the necessity of balance across various dimensions of family life, including physical, mental, financial, and social well-being. The research findings suggest that the integration of these two theories offers a more holistic framework for bolstering family resilience. Enhancing family resilience can be achieved through strategies that encompass open and effective communication, prudent financial management, comprehensive sexuality education, and active community engagement. Additionally, initiatives aimed at strengthening family resilience should also incorporate spiritual and moral dimensions, which are pivotal in maintaining equilibrium and harmony within family life. Conclusion: This study provides pragmatic recommendations for policymakers and community stakeholders in the development of intervention programs that support family resilience in the contemporary era.